2008
DOI: 10.1002/ange.200801579
|View full text |Cite
|
Sign up to set email alerts
|

Zur Reaktivität eines terminalen Chromborylenkomplexes gegenüber Olefinen – Boryleneinschub in eine C‐H‐Bindung

Abstract: Im sich rasch entwickelnden Feld der terminalen Borylenkomplexe beginnen sich erste faszinierende Reaktivitäts-muster abzuzeichnen, die stark von der partiellen oder vollständigen Spaltung der M=B-Bindung geprägt sind.[1] Von Bedeutung ist hier der Befund, dass terminale Gruppe-VIAminoborylenkomplexe die Boryleneinheit auf andere Übergangsmetalle übertragen, was maßgeblich zur Synthese neuer Borylenkomplexe beigetragen hat.[2] Vor kurzem berichteten wir über die Synthese von Aminoborirenen, die durch einen ähn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
18
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 47 publications
5
18
0
2
Order By: Relevance
“…[10] Borylene ligands can also be transferred photochemically from transition-metal complexes to unsaturated hydrocarbons, which can result in borirene formation [11] or CÀH insertion in the case of olefins. [12] Borylenes are subvalent boron counterparts of carbenes. A hallmark of carbenes is their facile addition to alkenes, a reaction that has received intense scrutiny.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Borylene ligands can also be transferred photochemically from transition-metal complexes to unsaturated hydrocarbons, which can result in borirene formation [11] or CÀH insertion in the case of olefins. [12] Borylenes are subvalent boron counterparts of carbenes. A hallmark of carbenes is their facile addition to alkenes, a reaction that has received intense scrutiny.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Des weiteren ist die Insertion des DB-R-Fragments in olefinische C-H-Bindungen beschrieben worden. [16] Ein besonders interessanter, jedoch unerforschter Bereich der Chemie von Übergangsmetall-Borylen-Komplexen ist deren Reaktivität gegenüber (oder Übertragung auf) Metall-Kohlenstoff-Mehrfachbindungen. Deshalb und aufgrund unseres Interesses an B-Amino-1-boraallenen (II) haben wir das Verhalten von terminalen Borylenkomplexen der Gruppe-6-Metalle gegenüber Vinylidenrhodiumkomplexen untersucht.…”
unclassified
“…[21,22] Braunschweig et al very recently reported access to a vinylborane by insertion of a borylene chromium complex into an olefinic CÀH bond. [23] The corresponding complex [Cr{HBN-(SiMe 3 ) 2 CH=CHCMe 3 }(CO) 4 ] was isolated and characterized as a formally chromium(0) olefin complex with a weak B À H coordination to the metal center. We now report the synthesis of two new boron-containing compounds, the phosphinomethyl(amino)borane Ph 2 PCH 2 BHNiPr 2 (1) and the lithium sulfido(methyl)borohydride Li[MeSCH 2 BH 2 Me] (2), as well as their coordination to the two ruthenium precursors [RuH 2 (h 2 -H 2 ) 2 (PCy 3 ) 2 ] (3) and [RuHCl(h 2 -H 2 )-(PCy 3 ) 2 ] (4).…”
mentioning
confidence: 99%